Improving the SGP: Taxes and Delegation rather than Fines - Assar Lindbeck; Dirk Niepelt (The Research Institute of Industrial Economics (IUI), 2004)
We analyze motivations for, and possible alternatives to, the Stability and Growth Pact (SGP). With regard to the former, we identify domestic policy failures and various cross-country spillover effects; with regard to the latter, we contrast an economic-theory perspective on optimal corrective measures with the legalistic perspective adopted in the SGP. We discuss the advantages of replacing the Pact's rigid rules backed by fines with corrective taxes (as far as spillover effects are concerned) and procedural rules and limited delegation of fiscal powers (as far as domestic policy failures are concerned). This would not only enhance the efficiency of the Pact, but also render it easier to enforce.
Keywords: E63; F33; F42; H60; 330; Stability and Growth Pact; Spillover Effects; Policy Failures; Pigouvian Taxes; Policy Delegation; Reform; Finanzpolitik; Internationale Wirtschaftspolitik; Spillover-Effekt; Internalisierung externer Effekte; Theorie; EU-Staaten; Europäischer Stabilitätsmechanismus